1987
DOI: 10.1152/ajpcell.1987.253.6.c835
|View full text |Cite
|
Sign up to set email alerts
|

Role of laminin in maintenance of type II pneumocyte morphology and function

Abstract: Loss of differentiated function by type II pneumocytes plated on plastic surfaces was demonstrated by decreased lamellar body content, increased cellular protein, and rapid cellular flattening, changes that were retarded modestly by plating cells on laminin-coated surfaces. Laminin surfaces also inhibited [3H]thymidine (THM) incorporation into cellular DNA by 40% compared with plastic at 40 h, but did not alter an additional mitogenic effect of rat serum over fetal calf serum. In contrast, cells plated on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…Previous studies have shown that heterogeneity exists in the composition of the basement membranes beneath type I and type I1 cells and that these differences may be important in regulating alveolar epithelial differentiation (Sannes, 1991). An important role for laminin in lung development has already been demonstrated in the process of branching morphogenesis and in the phenotypic maintenance of isolated alveolar type I1 cells in culture (Rannels et al, 1987;Schuger et al, 1990). However, the correlation between alveolar epithelial differentiation and the differential expression of the laminin chains in vivo has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that heterogeneity exists in the composition of the basement membranes beneath type I and type I1 cells and that these differences may be important in regulating alveolar epithelial differentiation (Sannes, 1991). An important role for laminin in lung development has already been demonstrated in the process of branching morphogenesis and in the phenotypic maintenance of isolated alveolar type I1 cells in culture (Rannels et al, 1987;Schuger et al, 1990). However, the correlation between alveolar epithelial differentiation and the differential expression of the laminin chains in vivo has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cultured type I1 cells lose functional characteristics, such as the ability to synthesize the lipid and protein components of surfactant (Shannon et al, 1987(Shannon et al, , 1990. However, when isolated type I1 cells are cultured on Matrigel, an extract of basement membrane proteins prepared from the EHS tumor (Timpl et al, 1979; as much as 80% of Matrigel total protein is laminin-1), the type I1 cells maintain the morphological and functional characteristics of the differentiated cell type (Rannels et al, 1987). There is a loss of laminin immunoreactivity around and under cultured type I1 cells that have begun to flatten and lose their differentiated phenotype (Rannels et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 48-h incorporation by cells cultured on plastic in 24-well culture plates, cells were rinsed twice with cold PBS, and DNA was precipitated with 5% TCA, dissolved in 200 l of 1 N sodium hydroxide, and neutralized by 200 l of 1 N acetic acid (28). After being scraped with the aid of a rubber policeman, 200-l aliquots were used to determine incorporated radioactivity in OptiPhase "Hisafe" scintillation cocktail (Wallac Scintillation Products, Perkin Elmer).…”
Section: H]thymidine Incorporation and 5-bromo-2ј-deoxyuridine Labelingmentioning
confidence: 99%
“…Neither do they divide in isolated cell culture (13,14). The normal morphology of Type II cells in vitro can be prolonged by plating onto exogenous extracellular matrices (ECM), such as laminin (15), collagen gels (16) or basement membrane derived from cultured cells (15,17), and other sources (18,19). Furthermore, macrophage-or fibroblast-derived factors are thought to influence the differentiated function of Type H cells in vitro (17,20).…”
Section: Introductionmentioning
confidence: 99%